An overview of the oil palm industry: challenges and some emerging opportunities for nanotechnology development - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Abu Seman, Idris (MDPI, 2020)
The increase in the world’s oil demand due to the rise of the global population urges more research into the production of sustainable vegetable oilseeds, among which palm oil is the most suitable candidate as it is the most efficient oilseed crop in the world. In an effort to drive the oil palm industry in the areas of food safety and security nanotechnology could offer a sustainable alternative. However, the utilization of nanotechnology in the oil palm industry is still limited. In this review, we aim to encourage the researchers to fully utilize nanotechnology as an alternative solution to tackle the challenges faced by the oil palm industry. Moreover, we also aim to highlight the opportunities for nanotechnology development in oil palm-based related research. The major points are as follows: (1) Nanosensing enables real-time monitoring of plantation status and crop progression, including soil, water and nutrient management, early pest/disease detection, and the spreading of pests/diseases. The use of nanosensing conveniently extends into advanced breeding topics, such as the development of disease-tolerant plants; (2) Nanotechnology could be the answer for the development of integrated management of pest and disease. Active agricultural ingredients can be entrapped or encapsulated into nanocarrier systems to improve their solubility, stability, enhance their efficient delivery to site-specific targets, with longer shelf life, and consequently improved efficacy; (3) Valuable nanomaterials can be isolated and generated from oil palm biomass waste. The utilization of oil palm biomass waste could overcome the issue of the massive production of waste in the oil palm industry and palm oil mills, where oil only accounts for 10% of the biomass, while 90% is comprised of the generated biowastes. (4) Palm oil can be utilized as a green alternative as a capping and stabilizing agent in the biosynthesis of metallic and non-metallic nanoparticles. In addition, nanoemulsion formulations using palm oil in drug delivery systems offer advantages such as low toxicity, enhance bioavailability and solubility of the drugs, apart from being inexpensive and environmentally friendly.